Frequency of Indirect Hyperbilirubinemia Requiring Exchange Transfusion, Etiology and its Immediate Outcome in Term Neonates in Neonatal ICU of National Institute of Child Health, Karachi - Sania Rafique, Mashal Khan, Mehmood Shaikh, Muhammad Hanif (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The present study assessed the frequency of causes of indirect hyperbilirubinemia (IH) requiring exchange transfusion and its immediate adverse events of exchange transfusion in term neonates. Methods: A prospective, observational study was undertaken at the Neonatal ICU of National Institute of Child Health, Karachi between July 2021 and December 2021. Term neonates arriving at the newborn unit of NICH with indirect hyperbilirubinemia were included in this study. All enrolled neonates were monitored for clinical, biochemical, and hematological adverse events for 7 days following exchange transfusion, and a predesigned performa was used to document observations. Results: Among 730 neonates with indirect hyperbilirubinemia, a total of 63 term neonates underwent exchange transfusion. The most common causes of hyperbilirubinemia were sepsis in 19 (30.2%) patients and ABO incompatibility in 13 (20.6%) patients. The most common adverse events noted were hypokalemia, which occurred in 10 (15.9%) and thrombocytopenia, which occurred in 10 (15.9%) cases. In six patients, sepsis developed. In total, five neonates died while four developed bilirubin encephalopathy. The total serum bilirubin and direct bilirubin among patients were significantly lowered after exchange transfusion (p<0.0001). There were no umbilical catheter-related complications. Bilirubin encephalopathy was present in 4 patients. There were five deaths, but not due to the procedure. Practical implication Conclusion: We highlighted the main causes of indirect hyperbilirubinemia as sepsis and ABO incompatibility in our setting. Furthermore, we also identified the immediate and short-term outcomes of exchange transfusion with a mortality rate of 7.9%. The overall outcome was favorable after the exchange transfusion. Keywords: Hyperbilirubinemia, kernicterus, exchange transfusion, indirect bilirubin, neonates , jaundice